Incorporação de ferro em fotocatalisadores de hidroxiapatitas aplicados à fotorredução de CO2 com H2 - Silva, Dyego dos Santos (2020)
The energy demand provided by socioeconomic growth, together with growing climate concerns, has encouraged the search for more sustainable energy alternatives. Faced with this scenario, the photocatalytic reduction of CO2 presents itself as an attractive alternative, because in addition to using CO2 as a raw material and producing fuels and chemicals with high added value, it also aims to employ a renewable energy source which is sunlight. In view of this, this work aims to contribute to the advancement in the development of materials to be used as photocatalysts. For this purpose, the behavior of iron-doped hydroxyapatites in a catalytic process of CO2 photoreduction with H2 was studied, using diffuse reflectance infrared Fourier transform spectroscopy. The photocatalysts had a specific surface in the range of 32.60-128.00 m2 .g-1 and bandgap energy values between 2.08 and 4.92 eV. The absence of segregated phases in the XRD results indicated the dispersion of iron in the hydroxyapatite structure. In the performance tests, the formation of H2O, CO and O2 was detected for all photocatalysts. From the evaluation of the infrared spectra, three possible reaction mechanisms have been suggested. Obtaining CH4 and C2H4 was observed for iron contents of 10 and 26.6%, indicating that hydroxyapatites with a high content of this metal are selective photocatalysts for the formation of hydrocarbons.